(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Pregnancy is a state of insulin resistance. Fasting serum C-peptide is used as an indicator of basal insulin secretion, which varies in different trimester in same individual. How the presence of gestational diabetes mellitus (GDM) affects insulin secretion is not well studied in Bangladeshi population. Objectives: To see the fasting serum C-peptide in subjects with GDM compared to age, body mass index (BMI), and trimester matched control with normal glucose tolerance (NGT) during pregnancy. Methods: This case-control study investigated fasting serum C-peptide in 72 pregnant women (GDM=37, NGT=35), and compared it between the study groups in different trimester and BMI category. GDM was diagnosed by WHO 2013 criteria. Plasma glucose was measured by the glucose oxidase method and C-peptide by a chemiluminescent immunometric assay. Results: Among the study participants with BMI ≥25 (n=40) (GDM=20, NGT=20), fasting serum C-peptides was significantly higher in the GDM group than that of the NGT NGT vs. GDM: 1.25 (0.94-1.82) vs. 1.67 (1.12-2.60); ng/ml, median with IQR, p=0.041 but no difference was observed between GDM and NGT with a BMI <25 kg/m2 NGT vs. GDM: 1.19 (0.93-1.53) vs. 1.24 (0.94-1.67); ng/ml, median with IQR, p=0.94. Within the NGT group, fasting C-peptide was similar with a BMI cut-off 25 kg/m2 (<25 vs. ≥ 25: 1.19 (0.93-1.53) vs. 1.25 (1.04-1.94); ng/ml, median with IQR, p=0.279, however, within the GDM group, the fasting C-peptide was significantly higher with a BMI ≥25 kg/m2 <25 vs. ≥ 25: 1.24 (0.94-1.67) vs. 2.35 (1.38-2.9); ng/ml, median with IQR, p=0.005. We did not observe any trimester-specific difference of fasting C-peptide between the NGT and the GDM (p=0.675, 0.073, and 0.247 for 1st, 2nd and 3rd respectively trimester), within NGT group (p=0.513) and within GDM group (p=0.489). Spearman’s correlation revealed positive and significant correlation between fasting C-peptide and BMI (rho=0.338, p=0.0041). Conclusion: Fasting C-peptide increased significantly in GDM with BMI ≥25 kg/m2, but not with <25kg/m2. J Assoc Clin Endocrinol Diabetol Bangladesh, January 2025;4(1): 9-14